The study of life quality parameters in children and adolescents with HIV associated tuberculosis - D. N. Аdzhablaeva (Туберкулез и болезни лёгких)
The objective of the study: to perform comparative assessment of life quality (LQ) associated with health of children and adolescents suffering from tuberculosis, both HIV negative and HIV positive.Subjects and methods. In 2017-2019, the cross-sectional epidemiological study was conducted in Pediatric Department of Samarkand Regional TB Dispensary, the study was aimed to assess life quality associated with health in 70 children and adolescents at the age from 5 to 18 years old. 35 of them had tuberculosis and HIV infection (TB/HIV Group), 35 had tuberculosis and negative HIV status. Pediatric Quality of Life Inventory – PedsQL was used to assess the life quality.Conclusion. The combination of HIV infection and tuberculosis has a more pronounced effect on the physical and mental functioning of patients and worsens the life quality of children and adolescents to a greater extent than tuberculosis.